Smart Parking System Model Analysis with NodeMCU and IoT-Based RFID - Sandhy Fernandez; Yetman Erwadi; Faisal Erlangga (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2023)
There is much conventional management parking nowadays. One of them is on campus 1 of Muhammadiyah University of Bengkulu. Many vehicles that do not belong to students or staff from the Muhammadiyah University of Bengkulu are parked in the inner area of campus. In addition, it causes vulnerable to direct physical contact with other people, while the government recommends not to have direct physical contact with other people in the era of the Covid-19 virus pandemic. So this study designs a smart parking system with Node MCU and IoT-based RFID. Parking systems that use RFID are able to filter incoming vehicles, increase security and efficiency in parking areas, and able to reduce the impact of the spread of the Covid-19 virus. The technology used is RFID as a user Id reader Sensor, Node MCU as a microcontroller, E-KTP as access to the parking area, servo as a parking portal driver, LCD as a sign whether access is accepted or not, and infrared as a distance sensor that will signal to a servo to close the portal. This system can be hoped to overcome the current problems.